Current status of the Xience V® everolimus-eluting coronary stent system. (October 2010) - Claessen, Bimmer E; Caixeta, Adriano; Henriques, José PS; Piek, Jan J
The introduction of drug-eluting stents has led to a marked reduction of restenosis, which is a major limitation of percutaneous coronary intervention for coronary artery disease. The next-generation Xience V ® (Abbott Vascular, CA, USA) everolimus-eluting stent was designed to address the limitations of first-generation drug-eluting stents. The cobalt–chromium stent platform with an open-cell design offers excellent deliverability. Moreover, the combination of a thin fluoropolymer eluting the antirestenotic drug everolimus provides both an effective suppression of neointimal tissue and rapid re-endothelialization above and between stent struts in preclinical studies. Large randomized clinical trials comparing the everolimus-eluting stent with the Taxus Express ® and Liberté ® (Boston Scientific, MA, USA) paclitaxel-eluting stents have shown reduced rates of repeat revascularization, myocardial infarction and stent thrombosis at 1-year follow-up with the everolimus-eluting stent. However, we will have to await long-term (5-year) data from these randomized clinical trials with the everolimus-eluting stent to determine whether the observed benefit is robust. Furthermore, data are currently limited the clinical performance of the everolimus-eluting stent relative to drug-eluting stents other than the Taxus Express and Liberté paclitaxel-eluting stents, although a large number of trials are now being conducted to address these questions. In this article, we provide a comprehensive overview of (pre)clinical studies with the everolimus-eluting stent.